The Influence of Product Presentation in Online Fashion Retail on Purchase Decisions with Shopping Lifestyle as a Moderating Variable - Zahratul Musyarrofah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study aims to analyze the influence of product presentation in online fashion retail on purchase decisions, with shopping lifestyle as a moderating variable. Data were collected from 205 respondents through a survey and analyzed using Structural Equation Modeling (SEM) version 26 to examine both direct and moderating effects. The analysis results show that coordinated product presentation (C.R. = 7.695; P = 0.000) and separated product presentation (C.R. = 5.716; P = 0.000) positively and significantly effect on purchase decisions. Additionally, the shopping lifestyle was found to moderate the effect of coordinated product presentation on purchase decisions (C.R. = 4.697; P = 0.000) and the impact of separated product presentation on purchase decisions (C.R. = 5.591; P = 0.000), where a more active shopping lifestyle strengthens the relationship between product presentation and purchase decision.